Comparison of hCG Versus Gonadotropin-Releasing Hormone Agonist to Induce Oocyte Maturation in Assisted Reproductive Technology Cycles: A Retrospective Cohort Study - Gulay Beydilli Nacak; Elif Tozkir; Enis Ozkaya; Ebru Cogendez; Fatih Kaya (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To compare some cycle characteristics and outcomes using a protocol consisting of a GnRH agonist trigger or hCG trigger after cotreatment with GnRH antagonist.